IMPLEMENTASI KEWENANGAN PENJAMINAN MUTU INTERNAL PERGURUAN TINGGI KEDINASAN BIDANG PEMASYARAKATAN - Markus Marselinus Soge; Lauditta Indahdewi (Jurnal Penjaminan Mutu, 2022)
The quality of higher education is obtained by implementing an internal quality assurance system carried out through the determination, implementation, evaluation, control, and improvement of higher education standards. The purpose of the research is to examine the sources of the internal quality assurance authority of the correctional higher education, and review the implementation of the internal quality assurance of the correctional higher education. Research methods are carried out by qualitative methods with data collection techniques in the form of observations and literature studies, then data were analyzed qualitative descriptive. The results of the research can be concluded first, the sources of authority for internal quality assurance of the correctional higher education are the Regulation of the Minister of Research, Technology and Higher Education Number 62 of 2016 concerning the Higher Education Quality Assurance System and the Regulation of the Minister of Law and Human Rights Number 27 of 2000 concerning the Statute of the Polytechnic of Correctional Sciences. The second, the implementation of the internal quality assurance authority of the correctional higher education is realized by the establishment of the Quality Assurance Unit organization, the preparation of internal quality assurance system documents, and the implementation of quality supervision.